Serological and molecular investigation for brucellosis in swine in selected districts of Uganda - Erume, J.; Roesel, Kristina; Dione, Michel M.; Ejobi, F.; Mboowa, G.; Kungu, Joseph M.; Akol, Joyce; Pezo, Danilo A.; El-Adawy, H.; Melzer, F.; Elschner, M.; Neubauer, H.; et al. (Springer, 2016)
Brucellosis is a notifiable zoonotic disease affecting livestock, humans, and wildlife in Uganda. Pigs can be infected with human pathogenic Brucella suis biovars 1 and 3 and can be a significant source of brucellosis for humans. Uganda has a rapidly growing pig population, and the pork consumption per capita is the highest in East Africa. The objective of this work was to determine the seroprevalence of brucellosis in Ugandan pigs. A cross-sectional serosurvey of pigs was conducted in three of the major pig-keeping districts in Uganda (Masaka (n = 381 samples), Mukono (n = 398), and Kamuli (n = 414)). In addition, pigs originating from these districts were sampled in the major pig abattoir in Kampala (n = 472). In total, 1665 serum samples were investigated by serological and molecular tests. Only three putative brucellosis-positive samples were detected serologically using indirect ELISA. These sera were found negative for Brucella antibodies by CFT; however, two had antibodies against Yersinia enterocolitica as determined by SAT. Presence of antibodies against Yersiniae was confirmed by Y. enterocolitica antibody-specific ELISA. The two Yersiniae ELISA-positive samples were brucellosis negative using real-time PCR. We tested additional 142 sera from the 1665 samples with real-time PCR. All tested negative. Under this type of production system, we expect a maximum B. suis prevalence of less than 1 % at 95 % confidence level, and therefore, the risk of acquiring brucellosis from the pigs or their products is negligible. However, pigs may harbor the zoonotic Y. enterocolitica. This is the first study to investigate the occurrence of brucellosis in pigs in Uganda and the first study to report Y. enterocolitica antibodies in swine in Uganda.